Two-dimensional metal polyphthalocyanine as well as preparation method and application thereof

The preparation of two-dimensional metal polyphthalocyanine materials through liquid phase peeling technology has solved the problems of low preparation efficiency and high cost in the prior art, and achieved the preparation of high yield and low cost ultra-thin two-dimensional metal polyphthalocyanine materials. Excellent rheology and catalytic activity.

CN119409967AInactive Publication Date: 2025-02-11BEIJING UNIV OF CHEM TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411682908.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing two-dimensional metal polyphthalocyanine synthesis methods have problems such as high cost, low preparation efficiency and difficulty in mass production, which limits its wide application in the fields of catalysis, sensing and flexible devices.

Method used

By preparing a solution containing a multi-layer block metal polyphthalocyanine material, polyvinylpyrrolidone and alkali metal ions, and applying mechanical action to perform liquid phase peeling, an ultra-thin two-dimensional metal polyphthalocyanine material was obtained.

Benefits of technology

The high yield and low cost preparation of two-dimensional metal polyphthalocyanine materials are achieved, with excellent rheology and printing applicability, and exhibit excellent conductivity, catalytic activity and sensing sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409967A_ABST
    Figure CN119409967A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of two-dimensional material preparation, and discloses a two-dimensional metal polyphthalocyanine material as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, preparing a solution containing a multi-layer blocky metal polyphthalocyanine material, polyvinylpyrrolidone and alkali metal ions, then applying mechanical action to the obtained solution, and carrying out liquid-phase stripping to obtain the two-dimensional metal polyphthalocyanine material. The invention also provides the two-dimensional metal polyphthalocyanine material obtained by the preparation method and application of the two-dimensional metal polyphthalocyanine material in preparation of high-concentration ink, electrocatalytic oxygen reduction reaction and construction of a nitrite electrochemical sensor. The ink form of the two-dimensional metal polyphthalocyanine material prepared by the invention shows excellent rheological property, is easy to process and apply, and shows excellent printing applicability; the material has higher conductivity, more accessible sites and larger specific surface area, shows excellent ORR activity, and also shows high sensitivity in a constructed nitrite electrochemical sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of two-dimensional material preparation, and in particular to a two-dimensional metal polyphthalocyanine and a preparation method and application thereof. Background Art

[0002] The two-dimensional characteristics of two-dimensional materials give them unique physical, electronic and chemical properties, making them have broad application prospects in electronic devices, energy fields and biomedicine. Flexible electronic technology is increasingly used in many fields such as wearable devices, smart sensors, and biomedicine. Among them, conductive ink, as one of the key materials of flexible electronic technology, has attracted much attention for its performance and application prospects. Two-dimensional nanosheets have become a promising ink material due to their unique properties.

[0003] Metal polyphthalocyanines have high thermal and chemical stability, and the metal nitrogen-carbon structure gives the material specific electronic properties and catalytic activity, making it widely used in catalysis, energy, and the environment. However, the π-π stacking layer structure similar to graphite limits axial electron transfer and the access of reactants to active sites. Two-dimensional metal polyphthalocyanines have higher conductivity, more accessible sites, and larger specific surface area, and can be better used in catalysis, sensing, and flexible devices.

[0004] Traditional synthesis methods of two-dimensional metal polyphthalocyanines, such as chemical vapor deposition and physical vapor deposition, have problems such as high cost, low preparation efficiency, and difficulty in large-scale production. Therefore, exploring new preparation technologies to achieve efficient and controllable synthesis of two-dimensional metal polyphthalocyanines has become one of the important directions of materials science research.

[0005] Therefore, developing a two-dimensional metal polyphthalocyanine material with better application effect and high yield and low cost preparation is of great significance for practical applications. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a two-dimensional metal polyphthalocyanine and a preparation method and application thereof. The two-dimensional metal polyphthalocyanine prepared by the present invention has the advantages of ultra-thinness, low cost and high yield.

[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a two-dimensional metal polyphthalocyanine material, wherein the method comprises the following steps:

[0008] (1) preparing a solution containing a multilayer bulk metal polyphthalocyanine material, polyvinyl pyrrolidone and an alkali metal ion;

[0009] (2) Applying mechanical action to the solution obtained in step (1) to perform liquid phase exfoliation to obtain a two-dimensional metal polyphthalocyanine material.

[0010] The second aspect of the present invention provides a two-dimensional metal polyphthalocyanine material obtained according to the preparation method described in the first aspect.

[0011] The third aspect of the present invention provides the use of the two-dimensional metal polyphthalocyanine material described in the second aspect in preparing high-concentration ink, electrocatalytic oxygen reduction reaction and constructing a nitrite electrochemical sensor.

[0012] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0013] (1) The present invention prepares ultra-thin two-dimensional metal polyphthalocyanine materials by liquid-phase exfoliation of multilayer blocky metal polyphthalocyanine materials with the assistance of polyvinyl pyrrolidone and alkali metal ions. The process is simple to operate, has high yield and low cost, and can realize large-scale production.

[0014] (2) The ink form of the two-dimensional metal polyphthalocyanine material prepared by the present invention exhibits excellent rheological properties, is easy to process and apply, and exhibits excellent printing applicability; the material has higher conductivity, more accessible sites and larger specific surface area, exhibits excellent ORR activity, and also exhibits high sensitivity in the constructed nitrite electrochemical sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a scanning electron microscope image of the multilayer blocky polyphthalocyanine cobalt prepared in step (1) of Example 1 of the present invention;

[0016] Figure 2 is a scanning electron microscope image of the two-dimensional cobalt polyphthalocyanine slurry prepared in step (4) of Example 1 of the present invention;

[0017] Figure 3 is a transmission electron microscope image of the two-dimensional cobalt polyphthalocyanine slurry prepared in step (4) of Example 1 of the present invention;

[0018] Figure 4 is an atomic force microscope image of the two-dimensional cobalt polyphthalocyanine slurry prepared in step (4) of Example 1 of the present invention;

[0019] Figure 5 The image is an image printed on a polyimide film by the high-concentration two-dimensional polyphthalocyanine cobalt slurry prepared in step (4) of Example 1 of the present invention;

[0020] Figure 6 This is a gram-level macro-preparation image of the two-dimensional cobalt polyphthalocyanine slurry prepared in Example 1 of the present invention;

[0021] Figure 7 is a particle size distribution diagram of the two-dimensional cobalt polyphthalocyanine prepared in Example 1 and Comparative Examples 1 and 2 of the present invention;

[0022] Figure 8The two-dimensional polyphthalocyanine cobalt prepared in Example 1, Comparative Examples 1 and 2 of the present invention is 5 mmol L -1 CV curve in sodium nitrite solution;

[0023] Fig. 9 1 is the LSV curve of the two-dimensional cobalt polyphthalocyanine prepared in Example 1 and Comparative Examples 1 and 2 of the present invention in 0.1 M KOH. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The first aspect of the present invention provides a method for preparing a two-dimensional metal polyphthalocyanine material, wherein the method comprises the following steps:

[0026] (1) preparing a solution containing a multilayer bulk metal polyphthalocyanine material, polyvinyl pyrrolidone and an alkali metal ion;

[0027] (2) Applying mechanical action to the solution obtained in step (1) to perform liquid phase exfoliation to obtain a two-dimensional metal polyphthalocyanine material.

[0028] In the present invention, a solution containing multilayer bulk metal polyphthalocyanine material, polyvinyl pyrrolidone and alkali metal ions is first prepared. In the solution, the multilayer bulk metal polyphthalocyanine material is dispersed in a polyvinyl pyrrolidone (PVP) solution in the presence of alkali metal ions. During this process, the alkali metal ions are inserted into the interlayer of the multilayer bulk metal polyphthalocyanine material to form an alkali ion intercalation compound. A mechanical action is then applied to it, and the van der Waals force between the metal polyphthalocyanine layers gradually weakens, and the alkali ion intercalation compound is stripped into a single layer or a few layers of two-dimensional metal polyphthalocyanine nanosheets. The added polyvinyl pyrrolidone can effectively avoid the problem of poor dispersion stability caused by the agglomeration of the nanosheets themselves.

[0029] The solution in step (1) can use water as a solvent. PVP can be first dispersed in water, and then multi-layer blocky metal polyphthalocyanine material and alkali metal salt are added in sequence to form a uniform solution.

[0030] The two-dimensional metal polyphthalocyanine material obtained by the present invention has an ultra-thin structure with a thickness of several atomic layers. The above structure effectively improves the utilization rate of active sites and exhibits excellent ORR electrocatalytic performance. The obtained two-dimensional metal polyphthalocyanine can also be prepared into high-concentration ink with excellent rheological properties for use in writing, screen printing and other fields. The constructed nitrite electrochemical sensor also exhibits high sensitivity.

[0031] According to some embodiments of the present invention, the multilayer bulk metal polyphthalocyanine material is obtained by the following method: mixing pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and a transition metal salt, and then calcining, washing and drying to obtain the multilayer bulk metal polyphthalocyanine material.

[0032] According to some embodiments of the present invention, the transition metal salt is selected from at least one of soluble salts of iron, cobalt, nickel and copper.

[0033] According to some embodiments of the present invention, the soluble salt is selected from at least one of nitrates, chlorides and sulfates.

[0034] According to some embodiments of the present invention, the calcination conditions include: a temperature of 180-300° C. and a time of 2-6 h.

[0035] According to some embodiments of the present invention, the washing is performed alternately with water, alcohol and acid.

[0036] According to some embodiments of the present invention, in the solution of step (1), the amount of polyvinyl pyrrolidone is 0.5-2.5wt%, preferably 1wt%, of the multilayer block metal polyphthalocyanine material. In the present invention, if the amount of polyvinyl pyrrolidone is too small, it is difficult to achieve the effect of stabilizing the dispersion; if the amount of polyvinyl pyrrolidone is too large, it is difficult to remove it in the subsequent purification process.

[0037] According to some embodiments of the present invention, the alkali metal ions in the solution of step (1) are derived from alkali metal salts, and the mass ratio of alkali metal salts to multilayer blocky metal polyphthalocyanine material is 1:20-1:1, preferably 1:2-10, preferably 1:5. In the present invention, if the amount of alkali metal salt is too small, the polyphthalocyanine is difficult to be effectively stripped; if the amount of alkali metal salt is too large, the stripping effect will not be significantly improved.

[0038] According to some embodiments of the present invention, the alkali metal ions are derived from an alkali metal salt, and the alkali metal salt is selected from at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide and cesium hydroxide.

[0039] According to some embodiments of the present invention, the alkali metal ion is selected from at least one of lithium ion, sodium ion, potassium ion, rubidium ion and cesium ion.

[0040] According to some embodiments of the present invention, the method of applying mechanical action in step (2) is selected from at least one of stirring, shearing, ball milling and ultrasound.

[0041] According to some embodiments of the present invention, the conditions for applying the mechanical action include: a power of 50-1000 W and a time of 0.5-4 h.

[0042] According to some embodiments of the present invention, after liquid phase stripping, two-dimensional metal polyphthalocyanine slurry or two-dimensional metal polyphthalocyanine powder is obtained by washing and drying. The two-dimensional metal polyphthalocyanine slurry can be used as a high-concentration ink for writing, screen printing and other fields; the two-dimensional metal polyphthalocyanine powder can be used as an electrocatalyst material and for constructing a nitrite electrochemical sensor.

[0043] According to some embodiments of the present invention, the concentration of the two-dimensional metal polyphthalocyanine slurry is 20-150 mg mL -1 .

[0044] According to some embodiments of the present invention, the washing is selected from one of suction filtration and dialysis.

[0045] According to some embodiments of the present invention, the washed dispersion is redispersed in isopropanol and then dried.

[0046] According to some embodiments of the present invention, the drying temperature is 60-100°C, preferably 80°C.

[0047] The second aspect of the present invention provides a two-dimensional metal polyphthalocyanine material obtained according to the preparation method described in the first aspect.

[0048] According to some embodiments of the present invention, the two-dimensional metal polyphthalocyanine material is a single-layer or few-layer structure.

[0049] According to some embodiments of the present invention, the thickness of the two-dimensional metal polyphthalocyanine material is less than 5 nm, preferably less than 2 nm.

[0050] According to some embodiments of the present invention, a lateral dimension of the two-dimensional metal polyphthalocyanine material is greater than 100 nm.

[0051] The third aspect of the present invention provides the use of the two-dimensional metal polyphthalocyanine material described in the second aspect in preparing high-concentration ink, electrocatalytic oxygen reduction reaction and constructing a nitrite electrochemical sensor.

[0052] The present invention will be described in detail below through examples.

[0053] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0054] Sources:

[0055] Polyvinylpyrrolidone (PVP): purchased from MacLean, average molecular weight 58000, product number P816205.

[0056] Example 1

[0057] This example is used to illustrate the preparation of two-dimensional cobalt polyphthalocyanine material.

[0058] (1) 3 g of pyromellitic anhydride, 6 g of urea, 1 g of ammonium chloride, 0.2 g of ammonium molybdate, and 1 g of cobalt chloride are uniformly mixed and calcined in a muffle furnace at 300° C. for 6 h; then the mixture is washed alternately with water, ethanol, and dilute hydrochloric acid three times, and dried in a vacuum drying oven overnight to obtain a multilayer block of cobalt polyphthalocyanine;

[0059] (2) 0.001 g of PVP was added to 100 mL of water, and after mixing, 0.2 g of multilayer block polyphthalocyanine cobalt and 0.01 g of lithium hydroxide were added in sequence, and the mixture was placed in a cell crusher, and ultrasonic liquid phase exfoliation was performed at a power of 100 W for 1 h to obtain a stable two-dimensional polyphthalocyanine cobalt dispersion; wherein the amount of PVP was 0.5% of the multilayer block polyphthalocyanine cobalt, and the mass ratio of lithium hydroxide to the multilayer block metal polyphthalocyanine material was 1:20;

[0060] (3) placing the obtained two-dimensional polyphthalocyanine cobalt dispersion in a dialysis bag until the pH value is neutral to obtain a purified two-dimensional polyphthalocyanine cobalt dispersion;

[0061] (4) Place the purified two-dimensional polyphthalocyanine cobalt dispersion in an oven at 80°C and adjust the dispersion concentration to 80 mg mL -1 , a high concentration of two-dimensional polyphthalocyanine cobalt slurry can be obtained, or two-dimensional polyphthalocyanine cobalt powder can be obtained by suction filtration and drying.

[0062] Example 2

[0063] This example is used to illustrate the preparation of a two-dimensional poly(copper phthalocyanine) material.

[0064] (1) 4 g of pyromellitic anhydride, 4 g of urea, 2 g of ammonium chloride, 0.1 g of ammonium molybdate, and 1 g of copper chloride are uniformly mixed and calcined in a muffle furnace at 200° C. for 2 h; then the mixture is washed alternately with water, ethanol, and dilute hydrochloric acid three times, and dried in a vacuum drying oven overnight to obtain a multilayer block of polyphthalocyanine copper;

[0065] (2) 0.02 g of PVP was added to 100 mL of water, and after mixing evenly, 2 g of multilayer block polyphthalocyanine copper and 0.02 g of sodium hydroxide were added in sequence, and the mixture was placed in a high-speed stirrer and stirred at a power of 800 W for 0.5 h to obtain a stable two-dimensional polyphthalocyanine copper dispersion; wherein the amount of PVP was 1% of the multilayer block polyphthalocyanine cobalt, and the mass ratio of sodium hydroxide to the multilayer block metal polyphthalocyanine material was 1:10;

[0066] (3) placing the obtained two-dimensional polyphthalocyanine copper dispersion in a dialysis bag until the pH value is neutral to obtain a purified two-dimensional polyphthalocyanine copper dispersion;

[0067] (4) Place the purified two-dimensional polyphthalocyanine copper dispersion in an oven at 80°C and adjust the dispersion concentration to 50 mg mL -1 , a high concentration of two-dimensional polyphthalocyanine copper slurry can be obtained, or two-dimensional polyphthalocyanine iron powder can be obtained by filtering and drying.

[0068] Example 3

[0069] This example is used to illustrate the preparation of two-dimensional poly(iron phthalocyanine) material.

[0070] (1) 3 g of pyromellitic anhydride, 2 g of urea, 1 g of ammonium chloride, 0.1 g of ammonium molybdate, and 0.8 g of ferrous chloride pentahydrate are uniformly mixed and calcined in a muffle furnace at 180° C. for 4 h; then, the mixture is washed alternately with water, ethanol, and dilute hydrochloric acid three times, and then dried in a vacuum drying oven overnight to obtain a multilayer block of polyphthalocyanine iron;

[0071] (2) 0.05 g of PVP was added to 100 mL of water, and after mixing evenly, 2 g of multilayer block polyphthalocyanine iron and 0.4 g of sodium hydroxide were added in sequence, and the mixture was placed in a ball mill and stirred at a power of 1200 W for 0.5 h to obtain a stable two-dimensional polyphthalocyanine iron dispersion; wherein the amount of PVP was 2.5% of the multilayer block polyphthalocyanine cobalt, and the mass ratio of sodium hydroxide to the multilayer block metal polyphthalocyanine material was 1:5;

[0072] (3) placing the obtained two-dimensional polyphthalocyanine iron dispersion in a dialysis bag until the pH value is neutral to obtain a purified two-dimensional polyphthalocyanine iron dispersion;

[0073] (4) Place the purified two-dimensional polyphthalocyanine iron dispersion in an oven at 80°C and adjust the dispersion concentration to 100 mg mL -1 , a high concentration of two-dimensional polyphthalocyanine iron slurry can be obtained, or two-dimensional polyphthalocyanine iron powder can be obtained by filtering and drying.

[0074] Example 4

[0075] (1) 2.9 g of pyromellitic anhydride, 5.0 g of urea, 1.2 g of ammonium chloride, 0.05 g of ammonium molybdate, and 0.8 g of ferrous chloride pentahydrate were uniformly mixed and calcined in a muffle furnace at 190° C. for 3 h; then, the mixture was washed alternately with water, ethanol, and dilute hydrochloric acid three times, and dried in a vacuum drying oven overnight to obtain a multilayer block of polyphthalocyanine iron;

[0076] (2) 0.01 g of PVP was added to 100 mL of water, and after mixing, 1 g of multilayer block polyphthalocyanine iron and 1 g of potassium hydroxide were added in sequence, and the mixture was placed in a ball mill and stirred at a power of 1200 W for 0.5 h to obtain a stable two-dimensional polyphthalocyanine iron dispersion; wherein the amount of PVP was 1% of the multilayer block polyphthalocyanine cobalt, and the mass ratio of potassium hydroxide to the multilayer block metal polyphthalocyanine material was 1:1;

[0077] (3) placing the obtained two-dimensional polyphthalocyanine iron dispersion in a dialysis bag until the pH value is neutral to obtain a purified two-dimensional polyphthalocyanine iron dispersion;

[0078] (4) Place the purified two-dimensional polyphthalocyanine iron dispersion in an oven at 80°C and adjust the dispersion concentration to 100 mg mL -1 , a high concentration of two-dimensional polyphthalocyanine iron slurry can be obtained; or two-dimensional polyphthalocyanine iron powder can be obtained by suction filtration and drying.

[0079] Example 5

[0080] (1) 3.2 g of pyromellitic anhydride, 6.0 g of urea, 2.8 g of ammonium chloride, 0.05 g of ammonium molybdate, and 1.3 g of ferrous chloride pentahydrate were uniformly mixed and calcined in a muffle furnace at 200° C. for 3 h; then, the mixture was washed alternately with water, ethanol, and dilute hydrochloric acid three times, and dried in a vacuum drying oven overnight to obtain a multilayer block of polyphthalocyanine iron;

[0081] (2) 0.01 g of PVP was added to 100 mL of water, and after mixing evenly, 1 g of multilayer block polyphthalocyanine iron and 0.5 g of potassium hydroxide were added in sequence, and the mixture was placed in a ball mill and stirred at a power of 1200 W for 0.5 h to obtain a stable two-dimensional polyphthalocyanine iron dispersion; wherein the amount of PVP was 1% of the multilayer block polyphthalocyanine cobalt, and the mass ratio of potassium hydroxide to the multilayer block metal polyphthalocyanine material was 1:2;

[0082] (3) placing the obtained two-dimensional polyphthalocyanine iron dispersion in a dialysis bag until the pH value is neutral to obtain a purified two-dimensional polyphthalocyanine iron dispersion;

[0083] (4) Place the purified two-dimensional polyphthalocyanine iron dispersion in an oven at 80°C and adjust the dispersion concentration to 100 mg mL -1 , a high concentration of two-dimensional polyphthalocyanine iron slurry can be obtained; or two-dimensional polyphthalocyanine iron powder can be obtained by suction filtration and drying.

[0084] Comparative Example 1

[0085] A two-dimensional polyphthalocyanine cobalt material was prepared using the method of Example 1, except that 0.011 g of PVP was used in step (2) and no lithium hydroxide was added.

[0086] Comparative Example 2

[0087] A two-dimensional polyphthalocyanine cobalt material was prepared using the method of Example 1, except that 0.011 g of lithium hydroxide was used in step (2) and no PVP was added.

[0088] Test Example 1

[0089] Figure 1 It shows that the polycobalt phthalocyanine prepared in step (1) of Example 1 is a multilayer block structure.

[0090] Figure 2 It shows that the two-dimensional polyphthalocyanine cobalt prepared in step (4) of Example 1 is relatively thin, and the porous alumina template substrate is visible, and wrinkles appear due to its thinness. Figure 3 The transmission electron microscope images also show the ultra-thin characteristics of two-dimensional poly(cobalt phthalocyanine). Figure 4 Atomic force microscopy images show that the thickness of the two-dimensional poly(cobalt phthalocyanine) is about 3 nm.

[0091] Figure 5 The printed pattern of the high-concentration two-dimensional cobalt polyphthalocyanine slurry prepared in step (4) of Example 1 on the polyimide film is shown. The pattern is clear, indicating that the printing adaptability as ink is good.

[0092] Figure 6 The gram-scale preparation of two-dimensional poly(cobalt phthalocyanine) slurry was demonstrated.

[0093] The test results of other embodiments are the same as those of embodiment 1.

[0094] Test Example 2

[0095] like Figure 7 As shown, the particle size of the samples peeled off from Example 1 and Comparative Examples 1-2 was evaluated using a laser particle size analyzer. PVP assisted alkali metal ion liquid phase peeling resulted in the smallest particle size of the two-dimensional material, and the presence of PVP and alkali metal ions had a synergistic peeling effect.

[0096] The test results of other embodiments are the same as those of embodiment 1.

[0097] Test Example 3

[0098] To further demonstrate the effect of the obtained two-dimensional metal polyphthalocyanine material, electrochemical detection of nitrite was carried out.

[0099] like Figure 8 As shown, at 5mmol·L-1 In the sodium nitrite solution, the two-dimensional polyphthalocyanine cobalt powders prepared in Comparative Example 1, Comparative Example 2 and Example 1 all showed NO2 - The oxidation peak caused by ion oxidation, the two-dimensional polyphthalocyanine cobalt modified electrode with PVP-assisted alkali metal ion stripping has a lower oxidation potential and a larger current (the peak above between 0.8-1.0 is the oxidation peak, and the corresponding potential (horizontal axis) is lower and the current (vertical axis) is larger), indicating that PVP and alkali metal ions have a better stripping effect synergistically.

[0100] The test results of other embodiments are the same as those of embodiment 1.

[0101] Test Example 4

[0102] The oxygen reduction performance of the samples was evaluated using a rotating ring disk electrode in 0.1 M KOH (loading 50 μg cm -2 ).

[0103] like Fig. 9 As shown, from the LSV curve at a rotation speed of 1600 rpm, it can be obtained that the sample after PVP-assisted alkali metal stripping in Example 1 has a larger half-wave potential and limiting current density than those in Comparative Examples 1 and 2.

[0104] The test results of other embodiments are the same as those of embodiment 1.

[0105] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a two-dimensional metal polyphthalocyanine material, characterized in that: The method comprises the following steps: (1) preparing a solution containing a multilayer bulk metal polyphthalocyanine material, polyvinyl pyrrolidone and an alkali metal ion; (2) Applying mechanical action to the solution obtained in step (1) to perform liquid phase exfoliation to obtain a two-dimensional metal polyphthalocyanine material.

2. The preparation method according to claim 1, wherein The multilayer block metal polyphthalocyanine material is obtained by the following method: mixing pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and a transition metal salt, and then calcining, washing and drying to obtain the multilayer block metal polyphthalocyanine material; Preferably, the transition metal salt is selected from at least one of soluble salts of iron, cobalt, nickel and copper; Preferably, the soluble salt is selected from at least one of nitrates, chlorides and sulfates; Preferably, the calcination conditions include: temperature of 180-300°C and time of 2-6h; Preferably, the washing is carried out alternately with water, alcohol and acid.

3. The preparation method according to claim 1 or 2, wherein: In the solution of step (1), the amount of polyvinyl pyrrolidone is 0.5-2.5wt% of the multilayer block metal polyphthalocyanine material, preferably 1wt%; Preferably, the alkali metal ions in the solution of step (1) are derived from alkali metal salts, and the mass ratio of the alkali metal salts to the multilayer bulk metal polyphthalocyanine material is 1:20-1:1, preferably 1:2-10, and preferably 1:

5.

4. The preparation method according to any one of claims 1 to 3, wherein The alkali metal ions are derived from alkali metal salts, and the alkali metal salts are selected from at least one of potassium hydroxide, lithium hydroxide, sodium hydroxide, rubidium hydroxide and cesium hydroxide; Preferably, the alkali metal ion is selected from at least one of lithium ion, sodium ion, potassium ion, rubidium ion and cesium ion.

5. The preparation method according to any one of claims 1 to 4, wherein The method of applying mechanical action in step (2) is selected from at least one of stirring, shearing, ball milling and ultrasound; Preferably, the conditions for applying the mechanical action include: power of 50-1000 W and time of 0.5-4 h.

6. The preparation method according to any one of claims 1 to 5, wherein After liquid phase stripping, two-dimensional metal polyphthalocyanine slurry or two-dimensional metal polyphthalocyanine powder is obtained through washing and drying; Preferably, the concentration of the two-dimensional metal polyphthalocyanine slurry is 20-150 mg mL -1 ; Preferably, the washing is selected from one of suction filtration and dialysis.

7. The preparation method according to claim 6, wherein: The washed dispersion is redispersed in isopropanol and then dried; Preferably, the drying temperature is 60-100°C, preferably 80°C.

8. The two-dimensional metal polyphthalocyanine material obtained by the preparation method according to any one of claims 1 to 7.

9. The two-dimensional metal polyphthalocyanine material according to claim 8, wherein: The two-dimensional metal polyphthalocyanine material is a single-layer or few-layer structure; Preferably, the thickness of the two-dimensional metal polyphthalocyanine material is less than 5 nm, preferably less than 2 nm; Preferably, the lateral size of the two-dimensional metal polyphthalocyanine material is greater than 100 nm.

10. Use of the two-dimensional metal polyphthalocyanine material according to claim 8 or 9 in preparing high-concentration ink, electrocatalytic oxygen reduction reaction and constructing nitrite electrochemical sensor.

Citation Information

Patent Citations

  • Preparation method of vanadium oxide serving as anode material of high-performance lithium ion battery

    CN108751256A

  • Method for efficiently preparing arsenene nanosheet

    CN113817927A

  • Two-dimensional polyphthalocyanine iron nanosheet as well as preparation method and application thereof

    CN118005936A